Pengaruh Tambahan Penghasilan Pegawai dan Gaya Kepemimpinan terhadap Disiplin Kerja Aparat Sipil Negara Bagian Umum Sekretariat Daerah Kota Prabumulih - Yos Karimudin; Zunaidah; M Rizki Ramadhan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of Additional Employee Income and Leadership Style on the Work Discipline of the General State Civil Apparatus of the Prabumulih City Setda. The population is the entire Civil Apparatus of the General State of Setda Kota Prabumulih which amounts to 40 people. Sampling using saturated sampling. The study used primary data obtained through questionnaires. Using multiple linear regression analysis methods and using SPSS release 24 software as an analysis tool. The results showed that Additional Employee Income and Leadership Style had a positive and significant effect on the Work Discipline of the General State Civil Apparatus of the Prabumulih City Setda simultaneously.